Synthesis and Bioactivities Study of Novel Pyridylpyrazol Amide Derivatives Containing Pyrimidine Motifs - Wu, Wenneng; Chen, Meihang; Fei, Qiang; Ge, Yonghui; Zhu, Yingying; Chen, Haijiang; Yang, Maofa; Ouyang, Guiping (Frontiers in Chemistry, 2020)
In this study, thirteen new pyridylpyrazolamide derivatives containing pyrimidine motifs were synthesized via six-step reactions. Bioassay results showed that some of the synthesized compounds revealed good antifungal properties against Sclerotinia sclerotiorum, Phytophthora infestans, Thanatephorus cucumeris, Gibberella zeae, Fusarium oxysporum, Cytospora mandshurica, Botryosphaeria dothidea, and Phompsis sp. at 50 μg/mL, which were similar to those of Kresoxim-methyl or Pyrimethanil. Meanwhile, bioassay results indicated that the synthesized compounds showed a certain insecticidal activity against Spodoptera litura, Mythimna separata, Pyrausta nubilalis, Tetranychus urticae, Rhopalosiphum maidis, and Nilaparvata lugens at 200 μg/mL, which was lower than that of Chlorantraniliprole. To the best of our knowledge, this study is the first report on the antifungal and insecticidal activities of pyridylpyrazol amide derivatives containing a pyrimidine moiety.